EPHA mutation as a predictor of immunotherapeutic efficacy in lung adenocarcinoma. Issue 2 (10th December 2020) - Bai, Hua; Duan, Jianchun; Li, Chengcheng; Xie, Wenzhuan; Fang, Wenfeng; Xu, Yu; Wang, Guoqiang; Wan, Rui; Sun, Jing; Xu, Jiachen; Wang, Xin; Fei, Kailun; et al.
Abstract : Background: Ephrin type-A receptors (EPHA) are members of family of receptor tyrosine kinases and are related to tumor immunogenicity and immune microenvironment, however, the association between EPHA mutation ( EPHA mut ) and efficacy of immune checkpoint inhibitors (ICIs) has not been investigated in non-small cell lung cancer (NSCLC). Methods: Multiple cohorts were used to assess the immunotherapeutic predictive performance of EPHA mut, including one discovery cohort (n=79) and two public validation cohort (cohort 1: NSCLC, n=165; cohort 2: pan-cancer, n=1662). The Cancer Genome Atlas cohort was used for prognostic analysis and mechanism exploration. Results: In the discovery cohort, patients with EPHA mut had superior disease control rate (72.2% vs 36.1%, p=0.01) and progression-free survival (PFS) (HR 0.38; 95% CI 0.21 to 0.68; p<0.001) compared with those with wide-type EPHA ( EPHA wt ) in NSCLC. The association between EPHA mut and immunotherapy outcomes in NSCLC was consistently observed in the validation cohorts by multivariable models (cohort 1, PFS HR 0.59; 95% CI 0.37 to 0.96; p=0.03; cohort 2, overall survival (OS) HR 0.63; 95% CI 0.41 to 0.98; p=0.04). Further pooled estimates of the discovery and validation cohorts showed that patients with EPHA mut exhibited a significantly longer PFS and OS in lung adenocarcinoma (LUAD) while not squamous cell lung cancer (LUSC). Consistently, mechanism analysis revealed that patients with EPHA mut was associated with increased T cell signatures and downregulated transforming growth factor-β signaling compared with patients with EPHA wt in LUAD while not LUSC. Conclusions: Our results demonstrated that EPHA mut is an independent classifier that could stratify patients with LUAD for ICIs therapy. Further prospective studies are warranted. Trial registration number: NCC2016JZ-03, NCC2018-092.